A randomized clinical trial of a human acellular dermal matrix demonstrated superior healing rates for chronic diabetic foot ulcers over conventional care and an active acellular dermal matrix comparator. Issue 3 (12th June 2017) - Cazzell, Shawn; Vayser, Dean; Pham, Hau; Walters, Jodi; Reyzelman, Alexander; Samsell, Brian; Dorsch, Kimberly; Moore, Mark
Abstract: This study compared the efficacy and safety of a human acellular dermal matrix (ADM), D‐ADM, with a conventional care arm and an active comparator human ADM arm, GJ‐ADM, for the treatment of chronic diabetic foot ulcers. The study design was a prospective, randomized controlled trial that enrolled 168 diabetic foot ulcer subjects in 13 centers across 9 states. Subjects in the ADM arms received one application but could receive one additional application of ADM if deemed necessary. Screen failures and early withdrawals left 53 subjects in the D‐ADM arm, 56 in the conventional care arm, and 23 in the GJ‐ADM arm (2:2:1 ratio). Subjects were followed through 24 weeks with major endpoints at Weeks 12, 16, and 24. Single application D‐ADM subjects showed significantly greater wound closure rates than conventional care at all three endpoints while all applications D‐ADM displayed a significantly higher healing rate than conventional care at Week 16 and Week 24. GJ‐ADM did not show a significantly greater healing rate over conventional care at any of these time points. A blinded, third party adjudicator analyzed healing at Week 12 and expressed "strong" agreement (κ = 0.837). Closed ulcers in the single application D‐ADM arm remained healed at a significantly greater rate than the conventional care arm at 4 weeks posttermination (100% vs. 86.7%; p  = 0.0435). There was no significant difference between GJ‐ADM and conventional care for healed wounds remaining closed. Single application D‐ADM demonstrated significantly greater average percent wound area reduction than conventional care for Weeks 2–24 while single application GJ‐ADM showed significantly greater wound area reduction over conventional care for Weeks 4–6, 9, and 11–12. D‐ADM demonstrated significantly greater wound healing, larger wound area reduction, and a better capability of keeping healed wounds closed than conventional care in the treatment of chronic DFUs.